P599 Development of an inflammatory bowel disease-specific nutrition screening tool (IBD-NST). (25th January 2019) - Wall, C; Wilson, B; Sanderson, J; Lomer, M
Abstract: Background: Patients with inflammatory bowel disease (IBD) frequently report that their nutritional concerns are unmet. Current nutrition screening tools identify malnourished patients with low body mass index (BMI) or significant weight loss but may not identify all IBD patients at nutrition risk. This study aimed to develop and test an IBD-specific nutrition self-screening tool (IBD-NST). Methods: IBD patients were recruited prospectively to independently complete IBD-NST and Malnutrition Universal Screening Tool (MUST). Subjective global assessment (SGA) and hand grip strength (HGS) were completed by a dietitian. The IBD-NST scored nutrition risk as low (0), moderate (1) or high (≥2), with equal importance given to BMI, unintentional weight loss, and a combination of active disease and nutrition concerns. Scores were compared with sub-optimal (15% below the mean) HGS, mid-upper arm muscle circumference (MAMC), BMI, weight loss >5% and SGA. χ 2 compared dichotomous outcomes and Receiver Operator Characteristic curves were used for prediction assessment with a cut-off of AUC < 0.7 for poor prediction. Results: 101/116 patients (87%) were recruited, 54 (53%) were female, 61 (60%) had CD, 33 (33%) had UC and 7 (7%) had IBD-U. Mean (SD) age was 40 (14) years and BMI was 24.6 kg/m 2 (4.3). SGA identified 11/91 (12%) with malnutrition and IBD-NST and MUST identified a similar number of patients at nutrition risk (Table 1). Twelve patients were low risk for MUST but high risk for IBD-NST due to having a flare and concerns about their nutrition. Unlike SGA and MUST, IBD-NST nutrition risk was not predicted by BMI (AUC = 0.262 (SE 0.06) (95% CI 0.17, 0.40)). No statistically significant difference in suboptimal HGS was seen across BMI categories of underweight (7/9 (78%)), healthy (28/46 (61%)), overweight (14/23 (61%)) and obese (6/12 (50%)). Patients with >5% weight loss (13/101 (13%)) or suboptimal HGS (56/101 (55%)) were significantly more likely to be at nutrition risk using IBD-NST, MUST and SGA ( p < 0.05). Patients with suboptimal MAMC (10/66 (15%)) were not significantly more likely to be at nutrition risk using IBD-NST or MUST ( p > 0.05). Conclusions: The IBD-NST identifies more patients with high nutrition risk, and equally weights physical, disease, and nutritional identifiers of nutrition risk and places less importance on BMI than SGA or MUST. Finally, we confirm that BMI is a poor indicator of HGS in IBD supporting a reduced importance in identifying nutrition risk. Further work is required to validate the IBD-NST.